(untitled) (Transactions of the Association of European Schools of Planning, 2021)
Understanding the relationships between a development and its wider setting is not new to planning. This often delicate balance has been contemplated by planners since well before the ground-breaking European Landscape Convention emerged in 2000. Nevertheless, and in the sustainable management of change, the ELC and its interpretations in domestic laws serve as conscious reminders of landscape as being more value-laden and complex than mere scenery. They support arguments for why meaningful engagement must and should be done - arguments that are most compelling during the education of young planners. In a world where rapid environmental change leads to more deadlines for decision-makers, and in which approaches to prescriptive environmental standards can result in mediocre compliance, it might seem idealistic to expect engagement with landscape in this way. Sharing experiences from University College Cork, this paper explores methods for equipping students with the skills necessary to make efficient and objective yet value-sensitive judgements on landscape at strategic and project levels.